In-vitro melanogenesis, cytotoxicity, and antioxidant activities of Peltophorum pterocarpum leaf extracts - Ana Sharmila Shafie,; Ahmad Hazri Abdul Rashid,; Theanmalar Masilamani,; Noor Syaffinaz Noor Mohamad Zin,; Nur Ain Sabrina Azmi,; Yong, Meng Goh; Nurdiana Samsulrizal, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Melanin is a protective pigment against cellular damage and skin cancer. Peltophorum pterocarpum has been used for centuries to treat skin diseases like eczema and psoriasis. However, whether P. pterocarpum leaf extract can affect melanin synthesis with the advantage of antioxidant defense against ultraviolet (UV) radiation remains to be investigated. We aimed to examine the melanogenesis, cytotoxicity, and antioxidant activities of P. pterocarpum leaf extracts. A two-dimensional (2D) cell culture model was employed to demonstrate the effect of P. pterocarpum extracts on melanin synthesis. The cell viability of B16-F1 melanoma cells was measured by Neutral Red Uptake (NRU) assay. Antioxidant activity was accessed using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2’,7’-dichlorodihydrofluorescein diacetate (DCFH-DA) assays. The ethanol extract of P. pterocarpum dose-dependently increased the melanin content and displayed cytotoxicity to B16-F1 melanoma cells at the highest concentration. In contrast, the equal amounts of the aqueous extract significantly inhibited melanin synthesis and did not show any cytotoxic effects on B16-F1 melanoma cells. The P. pterocarpum ethanol extract had a significantly higher total phenolic and flavonoid content than the aqueous extract and was more effective at scavenging DPPH free radicals and intracellular ROS induced by UVB, with IC50 of 519.24 ± 122.57 vs 1798.45 ± 143.09 μg/mL and 878.00 ± 23.50 vs 1379.00 ± 21.81 μg/mL, respectively. These findings suggest that the pro-melanogenic and anti-melanogenic activities of P. pterocarpum extract with antioxidant capacity against UVB-induced cellular damage are affected by the total phenolic and flavonoid contents.